2020
DOI: 10.1002/pat.4851
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of oligo‐glycerol based hydrolase responsive amphiphilic nanocarriers

Abstract: Herein, we report on the synthesis of a new class of novel non-ionic amphiphiles using triglycerol as a core, which is further functionalized with hydrophilic units poly(ethylene glycol) monomethyl ether (M n : 350 and 550) and a pair of hydrophobic alkyl chains (C 18 or C 15 ) via chemo-enzymatic approach. Fluorescence measurements and dynamic light scattering studies showed that all of the synthesized amphiphilic systems spontaneously self-assemble in aqueous solution, which is further confirmed by the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…The HLB value of all the amphiphiles was evaluated by the Griffin equation (Table 1). Furthermore, a comparison of these diaryloxydiglycerol based amphiphiles (15 and 16) having lower CAC with the previously reported triaryloxytriglyceryl analogue 19/20 synthesized by earlier reported method 35 shows that on moving from triaryloxytriglycerol spacer to diaryloxydiglycerol spacer reduces the CAC (Fig. 2 and Table 1) and this improvement in CAC may be because of proper structural balance of hydrophobic and hydrophilic segments.…”
Section: Physicochemical Characterization and Self-assembly Study Of mentioning
confidence: 62%
See 1 more Smart Citation
“…The HLB value of all the amphiphiles was evaluated by the Griffin equation (Table 1). Furthermore, a comparison of these diaryloxydiglycerol based amphiphiles (15 and 16) having lower CAC with the previously reported triaryloxytriglyceryl analogue 19/20 synthesized by earlier reported method 35 shows that on moving from triaryloxytriglycerol spacer to diaryloxydiglycerol spacer reduces the CAC (Fig. 2 and Table 1) and this improvement in CAC may be because of proper structural balance of hydrophobic and hydrophilic segments.…”
Section: Physicochemical Characterization and Self-assembly Study Of mentioning
confidence: 62%
“…Structure of (a) diaryloxydiglycerol based and (b)35 triaryloxytriglycerol based amphiphilic architectures.…”
mentioning
confidence: 99%
“…A novel-class of triglycerol based hydrolase responsive amphiphilic architectures were synthesized by using PEG as hydrophilic unit and alkyl chain (C 15 and C 18 ) as hydrophobic part, and employing chemo-enzymatic approach. 64 Fluorescence measurements and DLS studies showed that all the amphiphiles self-assembled in aqueous medium with low CAC in the order of 10 À5 M and DLS size in the range of 8-10 nm. Among all, amphiphiles having higher HLB value encapsulated the highest amount of drug nimodipine and dye nile red.…”
Section: Dendritic Amphiphilesmentioning
confidence: 95%
“…Our research group has been involved in the synthesis of advanced nanocarriers for drug delivery applications. We have synthesized numerous polymeric, 50-52 dendritic 48 and small amphiphilic architectures [53][54][55][56][57] for the encapsulation of various drugs and dyes. In one of our research works, water-soluble dendritic architectures having a symmetrical aromatic core, hydrophobic alkyl chain branches and glucose as hydrophilic surface groups were reported (Fig.…”
Section: Carbohydrate-based Amphiphiles As Drug/dye Nanocarriersmentioning
confidence: 99%